Relationship of Perceived Benefits and Perceived Barriers with Regular Physical Activity Among Employees of Mashhad University of Medical Sciences - Ali Vafaee-Najar; Hosein Ebrahimipour; Fatemeh Behzad; Hadi Tehrani (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: The development of technology in many developed communities has resulted in sedentary living and the appearance of many non-infectious diseases. In order to solve this problem and change the activity patterns, the factors affecting the physical activity should be clarified. This study tried to determine the benefits and perceived barriers of regular physical activities of the employees. Materials and methods: In this cross-sectional study, 117 employees of health center in Kalat, in Razavi Khorasan Province in Iran, affiliated with Mashhad University of Medical Sciences (MUMS), were studied in 2012-2013. In order to gather the data, a standard questionnaire of perceived benefits and barriers of physical activity was used. The data were analyzed using SPSS 16. Results: The average age of the employees were 34.09 ± 8.08 years and 66 of them (56.4%) were female. Overall, 34.2% of the employees had regular physical activity- 53% of male and 20% of female ones. The mean of perceived benefit scores was 100.3. ±1.4 and the mean of perceived barrier scores was 25.9±6.14. There was a significant relationship between physical activity and the age (p < 0.01) as well as the level of education (p < 0.01) but the presence or absence of physical activity had no significant relationship with the perceived benefits (p =0.58). Conclusion: Lack of adequate facilities for physical activities such as being far away, time-consuming and tiring due to exercise were the barriers for doing physical activities and some other factors like being interested in the exercises motivate the employees to do the physical activities. Paper Type: Research Article.